Regional Development Planning and Policy in the Aspects of Vulnerability and Disaster Resilient Cities: A Review - Latue, Theochrasia; Latue, Philia C; Sihasale, Daniel A; Rakuasa, Heinrich (Utan Kayu Publishing, 2023)
Disaster management in the world has undergone a paradigm change that is from responsive to preventive, from sectoral to multi-sector, from government responsibility solely to joint responsibility, centralization to decentralization and from emergency response to disaster risk reduction. Based on 6 directives of the President of the Republic of Indonesia delivered during the Rakornas PB (Disaster Management) at surabaya, February 2, 2019 one of which is